ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA SMKN 7 SEMARANG DALAM MENYELESAIKAN PERSAMAAN LINGKARAN BERDASARKAN KEMAMPUAN AWAL - Darojah, Naila Ulya; P, Agnita Siska; Muhtarom, Muhtarom; Kurniawati, Annisa (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The purpose of this research is to describe the numeracy literacy abilities of class XI TITL 2 students at SMKN 7 Semarang in solving circle equation problems based on initial abilities. The type of research used is qualitative research with descriptive methods. Subject selection is based on students' initial abilities based on the results of diagnostic test scores to categorize students' initial abilities into categories of students who have high initial abilities with a score criteria of 75 < score ≤ 100 , medium initial abilities with a score criteria of 35< score ≤ 75 and low initial abilities with a score criteria of 0 < score ≤ 35.Then 6 subjects were selected, each consisting of 2 student with high, medium and low initial ability. The instruments used in this research were numeracy literacy skills tests and interviews. The numeracy literacy ability test is presented in the test questions in the form of 2 numbered story questions and will be analyzed to reveal three indicators of numeracy literacy. The data collection analysis techniques used in this research are, 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results of the research show that: 1) students with high initial abilities are able to reveal all three indicators of numeracy literacy ability, 2) students with medium initial abilities are quite capable of fulfilling the first and second indicators of numeracy literacy ability, but are less able to fulfill the third indicator of numeracy literacy ability , 3) students with low initial abilities in solving circular equation problems are quite capable of meeting the first indicator of numeracy literacy ability, but are less able to fulfill the second and third indicators